How interventions to maintain services during the COVID-19 pandemic strengthened systems for delivery of maternal and child health services: a case-study of Wakiso District, Uganda - Steven Ndugwa Kabwama; Rhoda K. Wanyenze; Neda Razaz; John M. Ssenkusu; Tobias Alfvén; Helena Lindgren (Global Health Action)
Background Health systems are resilient if they absorb, adapt, and transform in response to shocks. Although absorptive and adaptive capacities have been demonstrated during the COVID-19 response, little has been documented about their transformability and strengthened service delivery systems. We aimed to describe improvements in maternal and child health service delivery as a result of investments during the COVID-19 response. Methods This was a descriptive case study conducted in Wakiso District in central Uganda. It included 21 nurses and midwives as key informants and 32 mothers in three focus group discussions. Data were collected using an interview guide following the Systems Engineering Initiative for Patient Safety theoretical framework for service delivery. Results Maternal and child health service delivery during the pandemic involved service provision without changes, service delivery with temporary changes and outcomes, and service delivery that resulted into sustained changes and outcomes. Temporary changes included patient schedule adjustments, community service delivery and negative outcomes such as increased workload and stigma against health workers. Sustained changes that strengthened service delivery included new infrastructure and supplies such as ambulances and equipment, new roles involving infection prevention and control, increased role of community health workers and outcomes such as improved workplace safety and teamwork. Conclusions In spite of the negative impact the COVID-19 pandemic had on health systems, it created the impetus to invest in system improvements. Investments such as new facility infrastructure and emergency medical services were leveraged to improve maternal and child health services delivery. The inter-departmental collaboration during the response to the COVID-19 pandemic resulted into an improved intra-hospital environment for other service delivery. However, there is a need to evaluate lessons beyond health facilities and whether these learnings are deliberately integrated into service delivery. Future responses should also address the psychological and physical impacts suffered by health workers to maintain service delivery.